2022
DOI: 10.3389/fimmu.2022.857308
|View full text |Cite
|
Sign up to set email alerts
|

GPC2 Is a Potential Diagnostic, Immunological, and Prognostic Biomarker in Pan-Cancer

Abstract: BackgroundGlypican 2 (GPC2), a member of glypican (GPC) family genes, produces proteoglycan with a glycosylphosphatidylinositol anchor. It has shown its ascending significance in multiple cancers such as neuroblastoma, malignant brain tumor, and small-cell lung cancer. However, no systematic pan-cancer analysis has been conducted to explore its function in diagnosis, prognosis, and immunological prediction.MethodsBy comprehensive use of datasets from The Cancer Genome Atlas (TCGA), Cancer Cell Line Encyclopedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 40 publications
0
47
0
Order By: Relevance
“…Total transcripts per million (TPM) expression profiles were obtained from the Cancer Cell Line Encyclopedia (CCLE) and Genotype-Tissue Expression (GTEx). 53 , 54 Log-normalized Stat3 and Fndc5 expression was qualified through Gencode V19 annotation. Stat3 and Fndc5 transcript values were analyzed with Pearsonā€™s correlation tests across multiple cell lines and organs using R version 4.0.0 (R Foundation for Statistical Computing).…”
Section: Methodsmentioning
confidence: 99%
“…Total transcripts per million (TPM) expression profiles were obtained from the Cancer Cell Line Encyclopedia (CCLE) and Genotype-Tissue Expression (GTEx). 53 , 54 Log-normalized Stat3 and Fndc5 expression was qualified through Gencode V19 annotation. Stat3 and Fndc5 transcript values were analyzed with Pearsonā€™s correlation tests across multiple cell lines and organs using R version 4.0.0 (R Foundation for Statistical Computing).…”
Section: Methodsmentioning
confidence: 99%
“…The Comparative Toxicogenomics Database (CTD, , accessed on 5 April 2022) integrates a large number of data on the interaction between chemical substances, genes, functional phenotypes, and diseases, which provides great convenience for the study of disease-related environmental exposure factors and the potential mechanism of drugs [ 74 ]. In the CTD database system, the keyword used was ā€œchemicalsā€ and gene interactions of 10 potential therapeutic drugs were searched.…”
Section: Methodsmentioning
confidence: 99%
“…The glycosylphosphatidylinositol anchor allows GPC, which is encoded by the glypican (GPC) family of genes, to bind to the cell membrane (23). A research showed GPC2 is a potential diagnostic, immunological, and prognostic biomarker (24). The importance of GPC2 in early detection, regulatory pathways, related genes, and chemicals has also been explored by researchers, who emphasized the extent to which it is expressed differently in cancer and healthy tissues (24).…”
Section: Gene Ratiomentioning
confidence: 99%
“…A research showed GPC2 is a potential diagnostic, immunological, and prognostic biomarker (24). The importance of GPC2 in early detection, regulatory pathways, related genes, and chemicals has also been explored by researchers, who emphasized the extent to which it is expressed differently in cancer and healthy tissues (24). Pancreatic cancer prognostic prediction using GPC2 combined with GPC3 and GPC5 has shown great efficacy (25).…”
Section: Gene Ratiomentioning
confidence: 99%